A compassion-focused approach to supporting change in patients with inflammatory bowel disease. (2nd May 2022) - Duff, Alexa
Abstract : Alexa Duff explores how to motivate change among patients with ulcerative colitis and Crohn's disease by activating their soothe and drive systems without stimulating their threat systems